If not a shaman, then what? Margie Gillis and trance - Cauthery, Bridget (Ethnologies, 2008)
AbstractReflecting on his fieldwork among the Malagasy speakers of Mayotte in the western Indian Ocean, Canadian anthropologist Michael Lambek questions why the West has such a “blind spot” when it comes to the human activity of trance. Querying the West’s blind spot has led me to argue that trance, as related in the ethnographic record, may be perceived as an attribute or characteristic of the Other. In this article, celebrated Canadian modern dancer Margie Gillis’ relationship with trance in her creative and performance practice is explored. Trance becomes an-Other entry point — one that has not been touched upon during Gillis’ lifetime — for interpreting both her role as a performer and her performing body.